Correlating active layer structure and composition with device performance and lifetime in amino acid modified perovskite solar cells - Lin,C-T; Xu,W; Macdonald,T; Ngiam,J; Kim,J-H; Du,T; Xu,S; Tuladhar,P; Kang,H; Lee,K; Durrant,J; McLachlan,M (ACS Applied Materials and Interfaces, 2021)
Additive engineering is emerging as a powerful strategy to further enhance the performance of perovskite solarcells (PSCs), with the incorporation of bulky cations and amino acid (AA) derivatives being shown as a promisingstrategy for enhanced device stability. However, the incorporation of such additives typically results inphotocurrent losses owing to their saturated carbon backbones hindering charge transport and collection. Herewe investigate the use of amino acids with varying carbon chain lengths as zwitterionic additives that enhancePSC device stability, in air and nitrogen, under illumination. We discover thatstability is insensitive to chain lengthhowever, as anticipated photocurrent drops as chain length increases. Using glycine as an additive results in animprovement in open circuit voltage from 1.10 to 1.14 V and a resulting power conversion efficiency of 20.2%(20.1% stabilized). Using time-of-flight secondary ion mass spectrometry we confirm that the AAs reside at thesurfaces and interfaces of our perovskite films and propose the mechanisms by which stability is enhanced. Wehighlight this with glycine as an additive, whereby an 8-fold increase in device lifetime in ambient air at 1-sunillumination is recorded. Short circuit photoluminescence quenching of complete devices are reported and revealthat the loss in photocurrent density observed with longer carbon chain AAs results from inefficient chargeextraction from the perovskite absorber layer. These combined results demonstrate new fundamentalunderstandings in the photophysical processes of additive engineering using amino acids and provide asignificant step forward in improving the stability of high-performance PSCs.